Across-Site Variation in Detection Thresholds and Maximum Comfortable Loudness Levels for Cochlear Implants - Pfingst, Bryan E.; Xu, Li (Journal of the Association for Research in Otolaryngology, 2004)
In cochlear implants, variation across stimulation sites in psychophysical detection thresholds (T levels) and maximum comfortable loudness levels (C levels) can be large when narrow-bipolar (BP) stimulation is used. This across-site variation is typically smaller when monopolar (MP) stimulation is used. At least two models can account for across-site variation and the effects of electrode configuration on the magnitude of the variation. According to one model, across-site variation reflects site-to-site differences in the distances between the stimulating electrodes and the sites of action-potential initiation. Under this model, the lower across-site variation with MP stimulation is due to shallower current versus distance gradients. An alternative model assumes that T and C levels depend on integration of activity across the whole population of neurons and that MP stimulation activates neurons over a larger spatial extent than does BP stimulation. If T and C levels are determined by integration of activity across large overlapping populations of neurons, then their values at adjacent sites should be more similar than if these levels result from integration across smaller, more independent populations. We tested the models by examining the effects on across-site variation of three variables believed to affect the spatial extent of activation: electrode configuration, stimulus level within the dynamic range, and electrode-array design. T levels and C levels were measured in 13 subjects with Nucleus CI24M (straight array) and 9 subjects with Nucleus CI24R(CS) (Contour) cochlear implants using bipolar (BP) and monopolar (MP) electrode configurations. Site-to-site variation in T and C levels for BP stimulation was 2.1-3.3 times larger than that for MP stimulation. Contrary to the across-neuron integration hypothesis, no significant differences were found between across-site variation for T levels and that for C levels for the BP configuration. There was considerable overlap in site-to-site variation values for the two types of implants but mean site-to-site variation in C levels for CI24M implants was significantly lower than that for CI24R(CS) implants. Control studies suggested that these results were not an artifact of the scale, and not due to differences in inherent variability of the psychophysical measures, or to the method of quantifying across-site variation.